Intentional Islanding Methods as Post Fault Remedial Action: A Review - N.Z. Saharuddin; Zainal Abidin; H. Mokhlis; K. Naidu (Institute of Advanced Engineering and Science, 2018)
Intentional islanding is the last defense mechanism executed to avoid cascading failures and total blackout in power system network during severe or critical contingency. It is performed when other mitigation techniques are unable to save the network from collapse. Intentional islanding is preferred compared to unintentional islanding, which produces unstable islands. The objective of intentional islanding is to split the network by disconnecting appropriate transmission lines to produce electrically stable and balanced islands. There are many methods suggested by previous researchers on intentional islanding. This paper presents a comprehensive review on various intentional islanding methods proposed based on the common objective function used which are minimal power imbalance and minimal power flow disruption. The paper focuses on five intentional islanding methods which are analytical, numerical, heuristic, meta-heuristic and hybrid approaches. This review paper will serve as guideline and reference for researchers to explore further in this topic of interest.